2009
DOI: 10.1176/appi.ps.60.11.1527
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nurse-Initiated Care in a Mental Health Crisis Assessment and Treatment Team in Australia

Abstract: The findings indicate that the nurse practitioner role can potentially initiate safe and effective mental health care and treatment that is as satisfying as that initiated by a physician. Additional, larger-scale research is required to determine the generalizability of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No statistical tests or numerical results reported Doyle (1994) [ 32 ] 3 Natural experiment with parallel groups: 1 Team in Folkestone, UK 1 Team in Barnet, UK Folkestone CRT with 9 am-5 pm opening hours No clear difference between CRT models reported and no statistical tests reported. Over the follow-up period Barnet CRT with 24 hour opening 9% of the 9-5 (Folkestone) CRT service users were admitted to hospital vs 5% Barnet Happell (2009) [ 33 ] 3 Natural experiment with pre- and post-comparison of parallel groups; Melbourne, Australia Control Group: Day after initial assessment, full assessment given by trainee psychiatrist , care management plan formulated. Mean HoNOS scores not significantly different between the groups at baseline – no p-values reported Treatment Group: Day after initial assessment, full assessment given by nurse practitioner , who took role of trainee psychiatrist (After 7 days service users in nurse-initiated care group reverted to treatment as usual) HoNoS scores for both groups significantly improved with treatment (difference for control group: t = 7.90, df = 51, p < .001; difference for treatment group: t = 6.90, df = 50, p < .001) No information given as to whether there was a significant difference between group HoNOS scores after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistical tests or numerical results reported Doyle (1994) [ 32 ] 3 Natural experiment with parallel groups: 1 Team in Folkestone, UK 1 Team in Barnet, UK Folkestone CRT with 9 am-5 pm opening hours No clear difference between CRT models reported and no statistical tests reported. Over the follow-up period Barnet CRT with 24 hour opening 9% of the 9-5 (Folkestone) CRT service users were admitted to hospital vs 5% Barnet Happell (2009) [ 33 ] 3 Natural experiment with pre- and post-comparison of parallel groups; Melbourne, Australia Control Group: Day after initial assessment, full assessment given by trainee psychiatrist , care management plan formulated. Mean HoNOS scores not significantly different between the groups at baseline – no p-values reported Treatment Group: Day after initial assessment, full assessment given by nurse practitioner , who took role of trainee psychiatrist (After 7 days service users in nurse-initiated care group reverted to treatment as usual) HoNoS scores for both groups significantly improved with treatment (difference for control group: t = 7.90, df = 51, p < .001; difference for treatment group: t = 6.90, df = 50, p < .001) No information given as to whether there was a significant difference between group HoNOS scores after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However the impact of this change in referral criteria on client or service outcomes was not evaluated. Three studies found no clear or significant difference between outcomes of the different CRT models regarding: organisational changes within the same team [ 31 ]; team opening times (9 am-5 pm versus 24-hours) [ 32 ]; and assessments by trainee psychiatrist versus by nurse practitioner [ 33 ].…”
Section: Resultsmentioning
confidence: 99%